A unique class of neutral cyclometalated platinum(ii) complexes with π-bonded benzenedithiolate: synthesis, molecular structures and tuning of luminescence properties. Issue 7 (12th January 2015) - Sesolis, Hugo; Moussa, Jamal; Gontard, Geoffrey; Jutand, Anny; Gullo, Maria Pia; Barbieri, Andrea; Amouri, Hani
Abstract : A unique class of luminescent neutral cyclometalated platinum(ii ) complexes2–4 with π-bonded benzenedithiolate are reported including two X-ray molecular structures. Abstract : A unique class of neutral cyclometalated platinum(ii ) complexes2–4 with π-bonded benzenedithiolate are reported including two X-ray molecular structures. To the best of our knowledge these are the first structures to be reported for cyclometalated platinum complexes with a benzenedithiolate ligand. All of the complexes are luminescent in fluid solution at room temperature and in frozen solvent glasses at 77 K and their emission properties can be tuned through ligand variation.